O passado (re)construído pela memória: análise de romance autobiográfico de Ângelo Bruno. - Lima, Ledisse Rocha (Universidade Federal do Tocantins, 2022)
In this paper, we analyze the book Duas pátrias, um só coração, by Italian-Brazilian writer Angelo Bruno (2009). By electing one of its authors, the research aims to contribute to understand and characterize the literary production made in Tocantins. The selected book is inscribed as a memory narrative, choosing the author to employ a third-person narrator, Lino, who would be Bruno's alter ego. It is divided into two moments of the author / character's ficctional: i. those lived in Italy, which involves the experience in World War II and his training as a seminarian; ii. those lived in Brazil, with particular emphasis on adventures in the north of Goiás, Xambioá, today Tocantins. As a main objective, we seek to identify the way this narrative as figurative these two places brought by memory. As specific objectives, we seek to contribute to the understanding of the literature produced in Tocantins; identify the characteristics of Angelo Bruno's prose; reflect on the writing of memory, and, finally, analyze aspects related to the culture and history of Tocantins in Bruno's book. As a methodology, our research consists of a bibliographical research, involving studies on memory and life histories and, to support the analysis we use authors who deal with the literature in Tocantins and the semiotic theory, which constitutes as theory of meaning. , privileging internal aspects of the text. As an engaged author, we see how his text serves to denounce social injustices committed here and there.